Home-based Anti-Tuberculosis Treatment Adverse Reactions (HATTAR) study: a protocol for a prospective observational study - Yang, Miaomiao (BMJ Open, 2019)
INTRODUCTION: Tuberculosis (TB) continues to be an important public health problem throughout much of the world. Drug treatment is the only effective treatment method, but adverse drug events (ADEs) and adverse drug reactions (ADRs) can affect medication adherence. As the number of drug-resistant TB patients and the number of anti-TB drugs have increased, it is necessary to explore the risk factors for ADEs/ADRs to reduce their occurrence. This study aims to build a home-based anti-TB treatment cohort and to recognise the incidences, prognosis and risk factors of anti-TB drug-induced ADEs/ADRs in real-world experiences. METHODS AND ANALYSIS: This study is a multicentre, prospective observational cohort study. The study population will consist of 3200 newly diagnosed TB patients between January 2019 and December 2020. After initiating the anti-TB treatment, all patients will be followed up until finishing treatment unless they withdraw, and we will record personal drug use and signs and/or symptoms of discomfort. Patients will receive scheduled laboratory tests in designated hospitals every 2 weeks during the first 2 months, and the residual blood sample after conducting the laboratory tests will be preserved. The ADEs/ADRs will be placed into eight categories: liver dysfunction, gastrointestinal reactions, drug allergy, arthralgia or muscle pain, nervous system disorders, haematological system disorders, renal impairment and others. ETHICS AND DISSEMINATION: This study protocol has been approved by the ethics committees of Nanjing Medical University. All patients will give written informed consent before enrollment. The findings of the study will be published in peer-reviewed journals and will be presented at national and international conferences.